INFORMATION AND COMMUNICATION MANAGEMENT STRATEGIES OF TELUK PATIPI DISTRICT GOVERNMENT IN COMMUNITY DEVELOPMENT - Muhammad Syihabuddin Abdurrazzaq; Abdul Ghoni (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2026)
Teluk Patipi District in Fakfak Regency, West Papua, faces complex governance challenges, particularly in ensuring transparency and accessibility of public information amid persistent infrastructure deficits. Comprising thirteen villages distributed across coastal and forested terrain, this district confronts severe limitations in electricity supply, internet connectivity, and inter-village transportation networks. Through an ethnographic approach and in-depth interviews conducted between August and December 2025, this study examines the adaptive strategies employed by the district government in managing and disseminating public information. Findings reveal three complementary strategies: face-to-face communication through monthly coordination meetings with village heads and door-to-door information visits; revitalization of traditional media including bulletin boards, mosque and church loudspeakers, kentongan (traditional percussion instruments), and official correspondence; and selective digital technology adoption through WhatsApp group optimization within signal-available zones. These strategies reflect contextual development communication principles, demonstrating that institutional effectiveness in remote areas is determined more by socio-cultural relevance than by technological sophistication.